The Roles of Solute Carriers in Auditory Function - Qian, Fuping; Jiang, Xiaoge; Chai, Renjie; Liu, Dong (Frontiers in Genetics, 2022)
Solute carriers (SLCs) are important transmembrane transporters, including 65 families of members. They play crucial roles in transporting many important molecules, such as ions and some metabolites, across the membrane, keeping the cellular homeostasis. SLCs also play important roles in hearing. It has been found that mutations in some of SLC members are associated with hearing loss. In this review, we summarized SLC family genes related with hearing dysfunction to reveal the vital roles of these transporters in auditory function. This summary could help us to understand the auditory physiology and the mechanisms of hearing loss, and further guide future study of deafness gene identification.